Strategi Pengembangan Desa Wisata melalui Pendekatan Analisis SWOT: Studi Kasus Tugu Utara, Kabupaten Bogor - Iwan Kurniawan; Laksmi Fitriani; Melati Dewi Asri; Ramdani Priatna (Jurnal Wacana Kinerja: Kajian Praktis-Akademis Kinerja dan Administrasi Pelayanan Publik, 2026)
This study explores the development strategy of Tugu Utara Tourism Village, Bogor Regency, using a SWOT analysis approach (Strengths, Weaknesses, Opportunities, Threats). The purpose of this research is to design an effective and sustainable strategy for rural tourism development by identifying the internal and external factors that influence it. The research method employed is a descriptive-qualitative approach, with data collection techniques including interviews, field observations, and document studies. The results indicate that Tugu Utara Village possesses abundant natural resources and high human resource potential but is still constrained by inadequate infrastructure, weak coordination among stakeholders, and limited financial support. The recommended strategy, based on the SWOT quadrant, is a diversification strategy that leverages existing strengths to address emerging threats. This research emphasizes the importance of collaboration between the community, government, and private partners in creating competitive and sustainable tourism products. The application of ecotourism principles has been gradually implemented as the foundation for developing the tourism village. In addition, enhancing human resource capacity, improving infrastructure, and utilizing information technology are key factors for the success of this strategy.